1974
DOI: 10.2113/gsecongeo.69.6.757
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Lead Isotopes to the Problems of Ore Genesis and Ore Prospect Evaluation: A Review

Abstract: Lead isotope data are now available not only for ores but also for cryptic rock leads from ultrabasic, oceanic and continental volcanic, granitic, metamorphic, oceanic-pelagic. and continental sedimentary rocks. The data show great application to problems of ore genesis and great promise in ore prospect evaluation.In ore genesis, the major applications are (1) in defining the source material for the lead in the ores and (2) in determining an estimate of the age of mineralization. As an example of each applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
3

Year Published

1980
1980
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(60 citation statements)
references
References 18 publications
2
55
0
3
Order By: Relevance
“…Using the parameter of Doe and Stacey (1974), the model ages of the ore minerals from different ore deposits were calculated, and the results are listed in Table 1. The model ages of the ore minerals are 1.92-2.07 Ga for the Tanyaokou, 1.95-2.07 Ga for the Dongshengmiao and 1.30-1.72 Ga for the Jiashengpan deposits.…”
Section: Lead Isotope Ratiosmentioning
confidence: 99%
“…Using the parameter of Doe and Stacey (1974), the model ages of the ore minerals from different ore deposits were calculated, and the results are listed in Table 1. The model ages of the ore minerals are 1.92-2.07 Ga for the Tanyaokou, 1.95-2.07 Ga for the Dongshengmiao and 1.30-1.72 Ga for the Jiashengpan deposits.…”
Section: Lead Isotope Ratiosmentioning
confidence: 99%
“…En .ettet le plomb possède quatr e isotopes sta bles qu i per met te nt de cara ctéri ser ses sou rces anthropiques et natu relles, grâce aux rappo rts isotopiques caractéristiques (signature) des différents gisements dont le plomb est issu . Chaque gisement possède une composition isotopique propre , qui est fonction de l'origine géographique et de l'âge du minerai [10]. Le rappo rt 206Pb/ 2o7 Pb mes uré dan s les princ ipa ux gise me nts mo ndia ux va rie da ns une lar ge ga mme allant de 0,897 pour Barbeton (Afrique du Sud), à 1,385 au Missouri (États -Unis).…”
Section: Analyse Des éChantillonsunclassified
“…Doe, 1970;Doe and Stacey, 1974) demonstrated that, except in the Mississippi Valley-type lead zinc and fluorite deposits, lead isotope data in many sedimentary rock-hosted stratiform deposits, such as the Kupferschiefer follow the singlestage growth curve, and their model age is identical to their host sedimentary rocks.…”
Section: Mat260mentioning
confidence: 99%
“…The model age from the ore lead is calculated by the method proposed by Doe and Stacey (1974). The parameters used for plotting single-stage growth curves and the isochrons of Fig.…”
Section: Mat260mentioning
confidence: 99%